2022
DOI: 10.3390/jof8020139
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Effect of Nutritional Imbalances of N and K on the Infection of Verticillium dahliae in Olive

Abstract: The effect of mineral nutrition on wilt diseases has been previously reported in many herbaceous hosts, though such an effect on Verticillium wilt in olive (Olea europaea L.; VWO), caused by Verticillium dahliae, is still uncertain. Field observations reveal that nitrogen (N) excess or imbalances of N-potassium (K) favour VWO epidemics. However, this has yet to be demonstrated. Thus, the aim of this study was to evaluate the influences of nutritional imbalances of N and K in V. dahliae infection of olive. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The V. dahliae isolates V323 (D pathotype) [40] and V004 (ND pathotype) [41] were used for this study. These isolates are maintained in the fungal collection of the Department of Agronomy at the University of Cordoba (UCO, Córdoba, Spain).…”
Section: Fungal Isolates and Culture Conditionsmentioning
confidence: 99%
“…The V. dahliae isolates V323 (D pathotype) [40] and V004 (ND pathotype) [41] were used for this study. These isolates are maintained in the fungal collection of the Department of Agronomy at the University of Cordoba (UCO, Córdoba, Spain).…”
Section: Fungal Isolates and Culture Conditionsmentioning
confidence: 99%
“…Together with the fact that efficient strategies to reduce the disease index or control the pathogen dispersal are scarce ( López-Moral et al., 2022 ), it can be assumed that olive growers are going to face V. dahliae -caused issues more sharply in the future. Recent biological studies start shedding light into the nutritional imbalances upon V. dahliae infection in olives, where potassium deficiency was found to increase the olive wilt disease progress ( López-Moral et al., 2022 ). This study is laying the foundation for further much needed work to help generation integrated pest management programs that may also include dedicated mineral nutrient management.…”
Section: Emerging Pests and Diseases Of Olive Treesmentioning
confidence: 99%
“…This study is laying the foundation for further much needed work to help generation integrated pest management programs that may also include dedicated mineral nutrient management. Similarly, recent trials with foliar and root application phosphonate salt copper phosphite (CuPh), which stimulates plant immunity and has antimicrobial properties, show some potential in olive trees ( López-Moral et al., 2022 ). Other strategies for V. dahliae control currently being evaluated in olives are the application of beneficial microbes including Aureobasidium pullulans AP08 and Bacillus amyloliquefaciens PAB-024 ( López-Moral et al., 2022 ).…”
Section: Emerging Pests and Diseases Of Olive Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Ca and Mg, two of the most influential elements in the CEC, are believed to play a key role in disease resistance as they aid in cell wall formation, increasing its resistance to attack by numerous enzymes and preventing pathogen penetration, as reported by Pennypacker (1989) [ 10 ]. Regarding this matter, recent research showed that, in the case of olive plants, treatments with N and Na excess, and with N and Na excess and K deficiency, decreased the germination of the fungus MS and the disease progress after artificial inoculations [ 11 ]. Soil texture also appears to have a variable effect on the pathogen, probably due to the complexity of existing interactions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%